Next generation integrated drive: a novel thermal and electrical integration technique for high power density converters used in automotive drive systems - Ahmadi, Behzad; Espina, Jordi; De Lillo, Liliana; Abebe, Robert; Empringham, Lee; Johnson, Christopher Mark (2018)
In this paper, an innovative method of electro-thermal integration of a drive system is presented. Important challenges of this integration consist of, firstly coupled thermal design of switching power modules and PM electric motor and secondly integration of high frequency switching devices into the motor housing, without compromising the performance of these transistors. To provide a solution to these challenges, an integrated liquid cooling system for both stator windings and transistor modules is designed. On the other hand, a specific module is designed to meet the specific requirements of this packaging technique.